UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN ARTIKULASI PADA SISWA KELAS X.IPA.3 SMAN 1 LEMBAH MELINTANG - rosma rosma (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the results of student learning X.IPA.3 Class SMAN 1 Valley Crossing in science sub reflikasi Describe the characteristics and the role of viruses in life was found that results for students in science sub reflikasi Describe the characteristics and the role of viruses in very kehidupanmasih low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in science sub reflikasi Describe the characteristics and the role of viruses in kehidupanmelalui Learning Model Articulation in Class X.IPA.3 SMAN 1 Valley Crossing West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 44 students Grades X.IPA.3 SMAN 1 Valley Crossing. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Learning Model Articulation can improve student learning outcomes in science sub reflikasi Describe the characteristics and the role of viruses in the life of SMAN 1 Valley Crossing. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 44.66 (less) increased to 85.64 (good) with an increase of 40.98%.